The relationship of school culture and parental involvement with grit among elementary students - Marcoleta, Kristel P. (College of Education, University of the Philippines Diliman, 2019)
The study explored the relationship of school culture and parental involvement with grit of elementary students. A total of 82 grades 4 to 6 students and their parents participated in the study. Correlation was done to understand the relationship between the variables. Simple linear regression was used to explore the extent to which relationships among school culture, parental involvement, and student grit are predictive. One-on-one interviews were also conducted to provide insight on reasons behind perception of parents on school culture, as well as the views of children on the involvement of parents in their education and their own grit as students. Results of the study revealed that parental involvement as performance goal orientation was not related to nor does it predict student grit as well as the student grit dimensions of perseverance of effort and consistency of interest. Parental involvement as mastery goal orientation was not associated with overall student grit. However, parental involvement as mastery goal orientation was found to have a weak, positive association to and predicted the perseverance of effort dimension of student grit. Conversely, parental involvement as mastery goal orientation was found to have a weak, inverse association to and negatively predicted consistency of interest. School culture was found to be related to and predict overall student grit and the dimension of consistency of interest. Further, school culture was not associated with student grit dimension of perseverance of effort. Interview results also show that the home and the school contribute to student grit. Messages that parents and the school communicate to children, activities that espouse value-laden, self-directed, independent learning, disposition of the teacher, parental support, and the continued partnership of the school and the home are means to drive student grit.